Is lifestyle modification effective for glycemic control among type II diabetic adults in Southeast Asia? - Htoo, Zaw Wai (Kansas State University, 2015)
Background: Type 2 diabetes mellitus (T2DM) is a costly and burdensome lifelong disease, and without proper glycemic control, severe life-threatening complications result. In Southeast Asia, the prevalence of T2DM is forecast to increase markedly from 2000 to 2030. Although literature reviews on lifestyle modification for glycemic control are available, these are mainly for the Western context, and there is a dearth of evidence for Southeast Asians who are at greater risk of T2DM and have differing patterns of diet, physical activity and body composition than Western populations. Objective: To systematically review literature on the effectiveness of lifestyle modification interventions for glycemic control in T2DM patients from Southeast Asia. Methods: Randomized controlled trials (RCT) with interventions ≥ 8 weeks that compared HbA1c or blood glucose for intervention (lifestyle modification) versus control groups were identified from searches in Cochrane Library, CINAHL, PubMed, ProQuest, Science Direct, SPORTDiscus, Scopus and Web of Science. Results: Seven RCTs (679 participants) meeting inclusion and exclusion criteria were identified. There was a significant reduction in HbA1c% (MD = -0.56%; 95% CI = -0.95,-0.16%; p = 0.006; n = 5 studies) and in blood glucose mg/dl (MD = -16.76 mg/dl; 95% CI = -31.36, -2.17 mg/dl; p = 0.02; n = 4 studies) over 3 months for lifestyle modification intervention groups. Lifestyle interventions included diet (n = 2), exercise (n = 2), and general lifestyle interventions (n = 3). Duration of interventions ranged from 12 weeks to 6 months. Studies included populations from Thailand (n = 5) and Malaysia (n = 2). Conclusion: Overall, lifestyle modification interventions are effective for the glycemic control of T2DM patients in countries of Southeast Asia.
Keywords: Type 2 diabetes mellitus; Glycemic control; HbA1c; Blood sugar level; Diet; Southeast Asia; Physical activity; Lifestyle modification; Medicine (0564); Nutrition (0570); Public Health (0573)